Философия физической культуры и спорта: перспективы метафизического подхода - Мицкевич, Наталья Ивановна (My University, 2016)
В статье рассматриваются подходы, существующие в философии физической культуры и спорта. Выделен и проанализирован метафизический подход. Показано антропологическое содержание метафизического подхода. Подчеркивается, что применение метафизического подхода в философских исследованиях физической культуры и спорта позволяет преодолеть ограничения сциентизма. In the article the approaches existing in philosophy of physical culture and sports are considered. The metaphysical approach is singled out and analyzed. The anthropological content of the metaphysical approach is shown. It is emphasized, that the application of the metaphysical approach in philosophical research of physical culture and sports allows to overcome limitations of scientism.
Keywords: физическая культура; метафизика; философская антропология; physical training; metaphysics; philosophical anthropology; кафедра фізичного виховання